Hereditary orotic aciduria identified by newborn screening - Staretz-Chacham, Orna; Damseh, Nadirah S.; Daas, Suha; Abu Salah, Nasser; Anikster, Yair; Barel, Ortal; Dumin, Elena; Fattal-Valevski, Aviva; Falik-Zaccai, Tzipora C.; Hershkovitz, Eli; Josefsberg, Sagi; Landau, Yuval; et al. (Frontiers in Genetics, 2023)
Introduction: Hereditary orotic aciduria is an extremely rare, autosomal recessive disease caused by deficiency of uridine monophosphate synthase. Untreated, affected individuals may develop refractory megaloblastic anemia, neurodevelopmental disabilities and crystalluria. Newborn screening has the potential to identify and enable treatment of affected individuals before they become significantly ill. Methods: Measuring orotic acid as part of expanded newborn screening using flow injection analysis tandem mass spectrometry. Results: Since the addition of orotic acid measurement to the Israeli routine newborn screening program, 1,492,439 neonates have been screened. The screen has identified ten Muslim Arab newborns that remain asymptomatic so far, with orotic acid elevated up to 10 times the upper reference limit. Urine organic acid testing confirmed the presence of orotic aciduria along with homozygous variations in the UMPS gene. Conclusions: Newborn screening measuring of orotic acid, now integrated into the routine tandem mass spectrometry panel, is capable of identifying neonates with hereditary orotic aciduria.